A Review of Scraping Therapy (Kerokan) as a Traditional Therapy in Medical Aspects - Nurhasanah, Lisa; Nurhikmah, Dieni; Rustanti, Riska Ayu (Faculty of Medicine, Universitas Airlangga, 2025)
Scraping therapy, also known as kerokan, is a traditional therapy practiced in East Asia for conditions like the common cold and musculoskeletal pain. While its mechanism of action (e.g., improved blood flow, reduced inflammation) suggests potential benefits, the effectiveness of scraping therapy requires further investigation. This review aimed to analyze the medical aspects of scraping therapy, including its efficacy, safety, and underlying mechanisms. We searched PubMed, ScienceDirect, Hindawi, and Scopus for studies published between 2014 and 2024 using keywords 'scraping therapy,' 'kerokan,' 'Gua-sha,' 'traditiona therapy,' and 'mechanism.' Studies were assessed using the Critical Appraisal Skills Programme qualitative checklist (CASP). Data will be analyzed using a thematic synthesis approach